2007
DOI: 10.3168/jds.2007-0054
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Heritability and Genetic Correlations for the Major Fatty Acids in Bovine Milk

Abstract: The current cattle selection program for dairy cattle in the Walloon region of Belgium does not consider the relative content of the different fatty acids (FA) in milk. However, interest by the local dairy industry in differentiated milk products is increasing. Therefore, farmers may be interested in selecting their animals based on the fat composition. The aim of this study was to evaluate the feasibility of genetic selection to improve the nutritional quality of bovine milk fat. The heritabilities and correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
136
13
22

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 124 publications
(213 citation statements)
references
References 20 publications
42
136
13
22
Order By: Relevance
“…All of these studies confirmed the existence of the genetic variability of the FA concentrations in bovine milk and fat, sug-gesting a potential future animal selection. Results obtained by Soyeurt et al (2007a) and Bobe et al (2008) and presented in Table 2 suggest that the concentrations of FAs in milk (expressed as g 100g -1 of milk and g L -1 of milk) are generally more heritable than the concentrations of FAs in milk fat (expressed as g 100g -1 of fat and %wt). Renner and Kosmack (1974a) also observed this trend.…”
Section: Individual Genetic Variabilitymentioning
confidence: 98%
See 4 more Smart Citations
“…All of these studies confirmed the existence of the genetic variability of the FA concentrations in bovine milk and fat, sug-gesting a potential future animal selection. Results obtained by Soyeurt et al (2007a) and Bobe et al (2008) and presented in Table 2 suggest that the concentrations of FAs in milk (expressed as g 100g -1 of milk and g L -1 of milk) are generally more heritable than the concentrations of FAs in milk fat (expressed as g 100g -1 of fat and %wt). Renner and Kosmack (1974a) also observed this trend.…”
Section: Individual Genetic Variabilitymentioning
confidence: 98%
“…Further, this model permits to take into account the performances of ancestors, descendants and collateral relatives, and thus improves the accuracy of the estimation. More recent studies, such as Soyeurt et al (2007a and2008b), Stoop et al (2008) and Bobe et al (2008), used an animal model to estimate the genetic parameters of FAs.…”
Section: Individual Genetic Variabilitymentioning
confidence: 99%
See 3 more Smart Citations